2018
DOI: 10.1007/s11528-018-0284-7
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Networked Collaborative Discourse: An UnLMS Approach

Abstract: Supporting collaborative discourse with discussion forums in a typical Learning Management System (LMS) remains challenging. This article reports on a design case of an "unLMS" approach, which aimed to devise a networked learning environment not based on an LMS for collaborative discourse in an online course. To support such discourse, four design principles were proposed based on the literature and then used to guide technological and pedagogical designs. Following the principles, a networked learning environ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Web objects, online platforms, and offline events (Chen, 2019). Finally, as our results showed, social and technological affordances have potential to cultivate a learning community in which the instructor can adopt a different set of approaches to provide a route for ongoing peer support, self-awareness, and social connection (Bereiter, 2002;Wise & Cui, 2018).…”
Section: More Coherent Communication Should Be Facilitated Among Multmentioning
confidence: 63%
See 1 more Smart Citation
“…Web objects, online platforms, and offline events (Chen, 2019). Finally, as our results showed, social and technological affordances have potential to cultivate a learning community in which the instructor can adopt a different set of approaches to provide a route for ongoing peer support, self-awareness, and social connection (Bereiter, 2002;Wise & Cui, 2018).…”
Section: More Coherent Communication Should Be Facilitated Among Multmentioning
confidence: 63%
“…facilitated via multiple channels, distributed in various locations, and accessed at varied times (Chen, 2019).…”
mentioning
confidence: 99%
“…Additionally, several studies suggested that dividing the class into smaller groups and pairing low-and high-performing students would also enhance discussion quality and interaction (Chen et al, 2019;. Hollett and Kalir (2017) and Chen (2019) highlighted the possibility of annotating "in the open" and engaging learning professionals' personal social media networks. A deliberately designed involvement plan can avoid unnecessary efforts for both the instructors and students and therefore promote learning.…”
Section: Decide the Level Of Instructor Involvementmentioning
confidence: 99%
“…In comparison with paper-based annotation, web annotation is not constrained by the need to simultaneously access a shared document and is posited to create a layer of interactivity on top of any web document (W3C Web Annotation Working Group, 2016). In education, web annotation is broadly used to support social reading, group sensemaking, knowledge construction, and community building (e.g., Chen, 2019;Kalir et al, 2020;Marshall, 1997;Plevinski et al, 2017). In the following sections, we first describe methodological details of the literature review, followed by a presentation of key findings.…”
Section: Introductionmentioning
confidence: 99%
“…We define OWA as digital annotation practices that embrace open web standards, advocate open principles, and nurture open practices online (Kalir, 2018). While not all OWA is civic writing (e.g., Chen, 2019), OWA can encourage opportunities for civic writing, just as civic writing can encourage the development of civic literacy. In this study, we approach educators’ use of OWA for public civic writing from a critical theoretical perspective that suggests that under certain conditions, OWA can foster critical and digital civic literacy.…”
Section: Introductionmentioning
confidence: 99%